2017
DOI: 10.1093/ckj/sfw112
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic nephropathy as the cause of end-stage kidney disease reported on the medical evidence form CMS2728 at a single center

Abstract: Background: End-stage renal disease (ESRD) incidence due to Type 2 diabetic nephropathy (DN) is 35–50%, according to the United States Renal Data System. Methods: A single-center, retrospective cohort study to determine incidence and diagnostic accuracy for Type 2 DN as the primary cause of ESRD (Code 250.40) on the Center for Medicare & Medicaid (CMS) Medical Evidence Report form (CMS2728) submitted at renal replacement therapy initiation. All patients  ≥18 years of age with a CMS2728 submitted between 1 Marc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 14 publications
1
40
0
4
Order By: Relevance
“…Patients with diabetes and advancing nephropathy are frequently labeled with diabetic kidney disease (DKD), despite awareness that they may have diabetes coincident with another etiology of kidney disease (10). Many patients with progressive DKD manifest heavy proteinuria, whereas others have early declines in eGFR without proteinuria.…”
Section: Limitations Of Esrd Classification On the Current Cms 2728 Formmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with diabetes and advancing nephropathy are frequently labeled with diabetic kidney disease (DKD), despite awareness that they may have diabetes coincident with another etiology of kidney disease (10). Many patients with progressive DKD manifest heavy proteinuria, whereas others have early declines in eGFR without proteinuria.…”
Section: Limitations Of Esrd Classification On the Current Cms 2728 Formmentioning
confidence: 99%
“…In individuals whose diabetes developed before nephropathy, it would be helpful to include diabetes duration before ESRD in Section 17 ("Co-Morbid Conditions") of the 2728 form. Shorter diabetes durations before onset of ESRD and lack of nonrenal microvascular complications (included in Section 17) suggest higher likelihoods of nondiabetes-associated ESRD (10).…”
Section: Future Opportunitiesmentioning
confidence: 99%
“…FGF23 inhibits 1-a hydroxylase gene with consequent decreased calcitriol synthesis. The previous study shown an inverse relationship between calcitriol and renin levels [29,30].…”
Section: Discussionmentioning
confidence: 91%
“…In this issue of CKJ , Yuan et al addressed the accuracy of a clinical diagnosis of DN among diabetic patients following the criteria proposed by the KDOQI guidelines [6]. Around 20% of patients did not meet KDOQI criteria for DN in type 2 DM, suggesting a significant overestimation of DN in this population.…”
mentioning
confidence: 99%
“…They showed that those patients lacking KDOQI-predicted DN were more likely to have an active urine sediment and less likely to have developed macroalbuminuria or retinopathy prior to end-stage renal disease. Using the binary logistic regression analysis, diabetic retinopathy was the only factor independently associated with patients who met KDOQI criteria [6]. …”
mentioning
confidence: 99%